(2x-1)(x+17)=0

Simple and best practice solution for (2x-1)(x+17)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-1)(x+17)=0 equation:



(2x-1)(x+17)=0
We multiply parentheses ..
(+2x^2+34x-1x-17)=0
We get rid of parentheses
2x^2+34x-1x-17=0
We add all the numbers together, and all the variables
2x^2+33x-17=0
a = 2; b = 33; c = -17;
Δ = b2-4ac
Δ = 332-4·2·(-17)
Δ = 1225
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1225}=35$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(33)-35}{2*2}=\frac{-68}{4} =-17 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(33)+35}{2*2}=\frac{2}{4} =1/2 $

You can always share this solution

See similar equations:

| 1+7p+p=1 | | 3(m+5)=12 | | 10(z+1)-5(z-2)=2(z-2)+2(z-1) | | (4a-1)=-23- | | 2(m-1)=-5(4m-m) | | -6w-14=8(w-7) | | 3(2x-3)-3=3(x-2)+9 | | X-0,15x=4800 | | (x-10)=-99 | | 1.5=1.2y=5.7 | | 2=10-3(x+7)+5(1-x)+6x | | X=7x-23 | | 4b÷8=20b= | | 4b÷8=20 | | 4.7x+2-4x=7+2x+4 | | 3-x/3=9/2 | | n+22=72 | | 8w?12=?5 | | (10x+9)=(4x+1) | | x^2?7x+2=0 | | 11x5=8x-6 | | 5(3m-2)-9(5-2m)=4m+2(5m+1) | | 2x2=300 | | 5(3m-2)-9(5-2m)=4m+2(5m+1 | | 3x+4=5-9 | | 9/x=98/7 | | 3x+17=32;3 | | 5x+3=15x+7 | | 261=152-v | | 5x+3+15x+7=180 | | 4x+5=17;3 | | 8/x^2-1-4/x-1=2/x+1 |

Equations solver categories